Breastfeeding and health outcomes in infants who receive continuing care from hospitals or community health centres in Chengdu Sichuan Province, People’s Republic of China - Yu, Chuan (Curtin University, 2013)
Introduction. The child health is one of the most important indicators of population health and the development of society. The health of children in China has improved in the past decades. The child health care system has been established and improved. The child health care service is one of the most important ways to improve child health and protect child from illness and growth failure. Infant feeding consultation, especially advice on breastfeeding practices, is one of the major parts of child health care services. The ongoing health system reform in China provides opportunity for the further development of child health care services. Besides hospital outpatient clinics, infants can receive child health care from community health centres with the development of more community health services in China.The aims of this study are to determine infant feeding practices in the city of Chengdu in Sichuan Province and the factors associated with breastfeeding practices, and explore the differences of child health care outcomes, including breastfeeding rates and health outcomes, of infants receiving their health care at a hospital or a community health centre. The maternal perceptions of quality of the child health care services provided will also be assessed.Method. A cohort study of 845 mothers and infants (417 in the hospital group and 428 in the community health group) who received continuing child health care from hospital or community health centre, was undertaken to explore the infant feeding practices in Chengdu and associated factors between April 2010 and January 2012. Mothers were interviewed face to face within 15 days after their infants" birth and followed up through phone interviews at one, three and six months using structured questionnaires. A client perception study was undertaken at six and half months postpartum to study the quality of the continuing child health care services provided by the hospital outpatient clinic and child health care section of community health centre.Descriptive and univariate analysis were used to describe the socio-demographic characteristics of the observations and facilities, the breastfeeding related variables and the prevalence of breastfeeding at one, three and six months between community health centre and hospital groups. Logistic regression analyses were used to examine the factors associated with infant feeding practices. Survival analysis was performed to describe the duration of breastfeeding and the factors associated with the breastfeeding duration. The factors relating to health outcomes including infants‟ growth and illnesses were analysed using ANOVA, Chi-square test, and a logistic regression model. The clients perceptions of the child health care from community health centres and hospitals were assessed by descriptive and univariate analyses. All analyses were undertaken using PASW Statistics version 18.0.Results In this study, 93% of mothers initiated any breastfeeding within 15 days postpartum. The any breastfeeding rate was 88.0%, 73.4% and 55.4% at one, three and six months. The full breastfeeding rate was 63.9% at baseline, and dropped to 60.5% and 52.9% at one and three months and was only 3.2% at six months. Most mothers introduced solid foods to their infants after four months. The exclusive breastfeeding rate was 12.5% within 15 days, 5.7% at one month and 1.7% at three month postpartum due to the high rates of usage of prelacteal feeds. Only one mother was still exclusively breastfeeding her baby at six months. The median duration of any breastfeeding in this study was 6.50 months.In this study, the second objective was to determine the health status of infants up to six months and the relationship with breastfeeding practices. The male and female infants had an average weight of 8.45±0.87 kg and 7.91±0.80 kg and average height of 68.4±2.05 cm and 66.9±1.95 cm at six months. Half of infants in the study had experienced health problem within six months after birth. About 89% of the infants who reported having a health problem were taken to see doctors and 9.8% of them were admitted to hospital. Any breastfeeding for less than one month and early introduction of solid food before four months were associated with a higher prevalence of lower respiratory tract infection in the study.A high rate of use of prelacteal feeds was found in this study. Only 24% of infants were given breastmilk as their first feed and more than 65% were given a first feed of infant formula. Five infants received cow milk as their first feed. About 9.6% of infants were given water, including plain water, sugar water and water with herbs as their first feed. Several factors were found to be associated with the use of prelacteal feeds in this study, including delivery method, the length of time for infant-to-breast contact after birth, teaching by hospital staff about positioning and attachment of infant at breast, health problems of mother during pregnancy, paternal education level and paternal preference of feeding method.The factors that were identified to be associated with the initiation of full breastfeeding in the study were mothers had a job, paternal education level was at least high school or occupational school, caesarean delivery, intended to go back work within six months, first feed with breastmilk, and most of mothers friends breastfed their babies. The determinants that were found to be associated with establishment of any breastfeeding were higher paternal education level, paternal job was office job, staff did not encourage early infant-to-breast contact, staff encouraged and supported breastfeeding, father did not care infants feeding method or preferred infant formula, maternal grandmother breastfed at least one infant. The predictors that showed an association with discontinuing any breastfeeding before 12 months in cox regression model were paternal smoking, mother back to work within six months, first feed with breastmilk, introduction of complementary food before four months, mother had experienced health problems by six months, health staff had any conflict opinion on breastfeeding, mother was satisfied with her breastfeeding experience at one month.Comparison of breastfeeding rate and health outcomes in infants received child health care from community health centre and hospital is another important aim of the study. The any breastfeeding rate was higher in infants who received child health care from a community health centre compared to the infants who received child health care from a hospital outpatient department at one and three months. The prevalence of lower respiratory tract infection was found to be higher in the hospital group than the community health centre group.Mothers' perceptions of child health care services were investigated using a structured client perception questionnaire. The average total perception scores of child health care services were 54.23 (95% CI 53.79-54.68) and 46.50 (95% CI 45.79-47.21) for community health centre group and hospital group. The level of approval was significant higher in the community health centre group. Significantly higher scores for the community health centre attendees were found in all four subscales. Mothers' evaluation showed that the child health care services in community health centre were preferred to the hospital outpatient services.Conclusion. This study provided information on breastfeeding rates and health status of infants in Chengdu. But more importantly, it provided evidence to support the continued development of child health care services in community health centres. The breastfeeding rate was found to be higher in infants who received child health care from community health centre in comparison with infants who received child health care from hospital outpatient clinics. There was no difference in the growth rates of infants in community health centre group compared to those infants from the hospital group. Compared with infants who received their child health care in hospital outpatient clinic, the prevalence of lower respiratory tract infection was lower in infants who received child health care in community health centres. The maternal perception score on child health care services and facility was higher in community health centre group than hospital group. These results provide support for the continuing support and expansion of child health care services in community health centre in preference to receiving regular child health care services from hospital outpatient departments. The promotion of child health care services in community health centres by the government will be beneficial to residents and their children.